Methodological bases of development of students innovative behaviour formation training - Pushkar, O; Fomichova, O. (Continuing Professional Education: Theory and Practice, 2019)
The paper formed the methodological basis for the organization and conduct of training on the formation of innovative behaviour of students, based on the model of formation of readiness of students to implement innovative behaviour and model of the innovation process (development of an innovative project) as a process of stimulating innovative behaviour. The readiness of students to implement innovative behaviour is seen as an active-activity state of the individual, which is influenced by the individual components such as: needs, motives and values of student (innovative consciousness), his innovative competence (knowledge, skills, abilities in innovation) qualities of innovative personality (creativity, curiosity, initiative, responsibility, ability to take risks, tolerance for ambiguity, etc.) and fixed in the minds the pattern of behaviour as a sequence of actions to develop and implement innovations in professional activities. On the basis of this thesis, the readiness to implement innovative behaviour includes psychological, cognitive and activity readiness. Model of the innovation process includes steps such as generating ideas, developing innovation, deployment and diffusion of this innovation. The task of the teacher is to implement these models in the learning process, particularly in conducting trainings, in order to create innovative behaviour of students. The article describes the training plan for the formation of innovative behaviour, based on the stages of the innovation process, as well as the tasks of teachers at each stage of the training. Additionally, the paper proposes methods employed the teacher at every stage of the innovation process, and rules on which training on the formation of innovative behaviour of students should be based.